ISOLATION AND ANTIBACTERIAL ACTIVITY TEST OF ASSOCIATED BACTERIA FROM MARINE SPONGE Tetilla sp. - Dian Pribadi Perkasa; Arie Budiyarto (Pusbindiklat - LIPI, 2012)
The marine sponge of Tetilla sp. collected near Gunung Kidul coast was studied for isolation of associated bacterial and its antibacterial activity. Sixteen bacterial strains were isolated from sponge Tetilla sp., four isolates among it showed ability to produce antibacterial metabolite. Cell extract of isolates were tested for antibacterial activity against Escherichia coli and Staphylococcus aureus using disc diffusion agar method. Cells extract of four selected isolate from late exponential phase and stationary phase broth culture showed antibacterial activity against Escherichia coli and Staphylococcus aureus. Thin layer chromatography analysis detected alkaloid and terpenoid in cell extract from stationary phase of isolates culture and none of it was detected in cell extract from late exponential phase of isolates culture.